Household Characteristic of Public Distribution System Beneficiaries and Per Capita Monthly Off-Take of Subsidized Rice in Arunachal Pradesh: With Reference to East and West Siang Districts - Lige Sora (Dera Natung Government College Research Journal)
Public Distribution System is a welfare program through which highly subsidize food and non-food grains are allocate to the identified households. As such under this program the beneficiaries are identified into four categories viz; Above Poverty Line (APL), Below Poverty Line (BPL), Antyodaya Anna Yojana (AAY) and Annapurna. Rice is one of the staple food grains of Arunachal Pradesh. Therefore, present paper ponders only on per capita monthly off-take of subsidized rice from the Public Distribution System program in Arunachal Pradesh.